Charge transfer and weak bonding between molecular oxygen and graphene zigzag edges at low temperatures. (October 2016) - Boukhvalov, D.W.; Osipov, V.Yu.; Shames, A.I.; Takai, K.; Hayashi, T.; Enoki, T.
Abstract: Electron paramagnetic resonance (EPR) study of air-physisorbed defective carbon nano-onions evidences in favor of microwave assisted formation of weakly-bound paramagnetic complexes comprising negatively-charged O2 − ions and edge carbon atoms carrying π-electronic spins. These complexes being located on the graphene edges are stable at low temperatures but irreversibly dissociate at temperatures above 50–60 K. These EPR findings are justified by density functional theory (DFT) calculations demonstrating transfer of an electron from the zigzag edge of graphene-like material to oxygen molecule physisorbed on the graphene sheet edge. This charge transfer causes changing the spin state of the adsorbed oxygen molecule from S  = 1 to S  = 1/2 one. DFT calculations show significant changes of adsorption energy of oxygen molecule and robustness of the charge transfer to variations of the graphene-like substrate morphology (flat and corrugated mono- and bi-layered graphene) as well as edges' passivation. The presence of H- and COOH- terminated edge carbon sites with such a corrugated substrate morphology allows formation of ZE–O2 − paramagnetic complexes characterized by small (<50 meV) binding energies and also explains their irreversible dissociation as revealed by EPR.